2014
DOI: 10.1007/s00268-014-2683-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Trocar‐Specific Morbidity in Laparoscopy

Abstract: Specific trocar morbidity is low and almost negligible for 5 mm trocars. The umbilicus appears to be an unfavorable TS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The TSIH rate can change depending on the type of trocar and its location. TSIH have been described at any location, but those situated at the10mm trocar are the most frequent (9,10,(12)(13)(14). It seems that for 5 mm trocars facial closure should not be necessary, but for ≥ 10 mm trocars it would be mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…The TSIH rate can change depending on the type of trocar and its location. TSIH have been described at any location, but those situated at the10mm trocar are the most frequent (9,10,(12)(13)(14). It seems that for 5 mm trocars facial closure should not be necessary, but for ≥ 10 mm trocars it would be mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the traditional OR for inguinal hernia, inguinal crease incision is considered to be scarcely visible because it is along the skin crease and usually is concealed under the cloths. On the other hand, umbilical incision for laparoscopy can cause umbilical deformities like protrusion, especially in reduced port surgery [ 15 ]. Moreover, in this study, the incidence of SSI was significantly higher in SILPEC than in OR group.…”
Section: Discussionmentioning
confidence: 99%
“…They have further reported that bleeding was from the 12-mm port site in 14 patients and 5 mm port site in the remaining 3 patients. Complications such as bleeding and hernia can increase as port diameter increases (3,8).…”
Section: Discussionmentioning
confidence: 99%